DAMPAK KEGIATAN PERAMBAHAN HUTAN PINUS REBOISASI TERHADAP SIFAT FISIK, KIMIA DAN BIOLOGI TANAH DI KAWASAN LINDUNG DANAU TOBA, SUMATERA UTARA - Basuki Wasis; Izudin . (Media Konservasi, 2012)
Encroachment is one of the causes of damage to pine forests. Forest damage can cause damage to soil properties on forest land that was left after the pine forest encroachment activities. This research was conducted aiming to determine the change of physical properties, chemical properties and biological properties of soil in the pine forest encroachment caused by activities in the area of pine forest reforestation in protected areas of Lake Toba, North Sumatra. Soil sampling conducted in purposive sampling in a pine forest and open land. The study was conducted on three plots in the pine forest and open land with the size of each 20 mx 20 m (0.04 ha). In the plot is made of three subplots with a size of 1m x 1m is placed randomly for soil sampling. Observations suggest that damage to the pine forest vegetation has caused the loss of top soil layer of soil, destruction of soil structure and the increase in soil erosion. Destruction of pine forest into open land has caused damage to soil physical properties as well as significantly decreasing soil chemical properties and biological properties of soil. Forms of soil degradation caused by damage to pine forests, which is an increase in soil density (density Limbak) of 129%, a decrease of 68% organic C and soil nitrogen decreased by 23%. The main factors causing soil degradation is logging the pine forest vegetation, soil organic matter decline and erosion. Keywords: forest encroachment, pine forests, open land, protected area,  soil properties.